The Transcriptional and Protein Profile From Human Infected Neuroprogenitor Cells Is Strongly Correlated to Zika Virus Microcephaly Cytokines Phenotype Evidencing a Persistent Inflammation in the CNS - Lima, Morganna C.; Mendonça, Leila R. de; Rezende, Antonio M.; Carrera, Raquel M.; Aníbal-Silva, Conceição E.; Demers, Matthew; D'Aiuto, Leonardo; Wood, Joel; Chowdari, Kodavali V.; Griffiths, Michael; Lucena-Araujo, Antonio R.; Barral-Netto, Manoel; et al. (Frontiers in Immunology, 2019)
Zika virus (ZIKV) infection during pregnancy is associated with microcephaly, a congenital malformation resulting from neuroinflammation and direct effects of virus replication on the developing central nervous system (CNS). However, the exact changes in the affected CNS remain unknown. Here, we show by transcriptome analysis (at 48 hours post-infection) and multiplex immune profiling that human induced-neuroprogenitor stem cells (hiNPCs) respond to ZIKV infection with a strong induction of type I interferons (IFNs) and several type I IFNs stimulated genes (ISGs), notably cytokines and the pro-apoptotic chemokines CXCL9 and CXCL10. By comparing the inflammatory profile induced by a ZIKV Brazilian strain with an ancestral strain isolated from Cambodia in 2010, we observed that the response magnitude differs among them. Compared to ZIKV/Cambodia, the experimental infection of hiNPCs with ZIKV/Brazil resulted in a diminished induction of ISGs and lower induction of several cytokines (IFN-α, IL-1α/β, IL-6, IL-8, and IL-15), consequently favoring virus replication. From ZIKV-confirmed infant microcephaly cases, we detected a similar profile characterized by the presence of IFN-α, CXCL10, and CXCL9 in cerebrospinal fluid (CSF) samples collected after birth, evidencing a sustained CNS inflammation. Altogether, our data suggest that the CNS may be directly affected due to an unbalanced and chronic local inflammatory response, elicited by ZIKV infection, which contributes to damage to the fetal brain.